A measurement of the B0s lifetime using reconstructed D-s mesons - Ackerstaff,K; Alexander,G; Allison,J; Altekamp,N; Anderson,KJ; Anderson,S; Arcelli,S; Asai,S; Axen,D; Azuelos,G; Ball,AH; Barberio,E; et al. (European Physical Journal C, 1998)
We report a measurement of the B0s meson lifetime from B0s → D-sX decays, where D-s mesons are reconstructed in the D-s → φπ- and D-s → K0K- decay channels. From approximately 3.7 million hadronic Z0 decays recorded by the OPAL detector at LEP a sample is selected containing 911 ± 83 candidates, of which 519 ± 136 are estimated to be from B0s meson decays. Fitting the distribution of the distance from the beam spot to the decay vertex of the D-s candidates with an unbinned likelihood function we measure π(B0s) = 1 72+0.20+0.18-0.19-0.17 ps, where the errors are statistical and systematic, respectively.